Prevalence, motivations, lifestyle preferences, and basic health behavior among 1,350 vegan, vegetarian, and omnivorous Austrian school teachers and principals - Wirnitzer, Katharina C.; Tanous, Derrick R.; Drenowatz, Clemens; Wirnitzer, Gerold; Schätzer, Manuel; Ruedl, Gerhard; Kirschner, Werner (Frontiers in Nutrition, 2025)
IntroductionFew European and Austrian adults live a healthy lifestyle. As critical role models, school teachers and principals are highly influential for delivering basic health education to children and adolescents.ObjectiveThis investigation aimed to analyze the underlying motivations and lifestyle preferences for diet type adherence among school teachers and principals and the associations with basic health behavior.MethodsThe present study followed a cross-sectional design. School teachers and principals in Austria fill out an online questionnaire, with questions on anthropometrics, physical activity levels, dietary behavior, and alcohol and smoking consumption. Statistical analysis was conducted with ANOVA and chi-squared tests.ResultsThe final sample included 1,350 participants (409 males, 941 females) with an average age of 45.8 ± 11.4 years. Health (46.4%) was the most important reason for dietary choice and sports engagement, and lifestyle (pooled 81.7%) the predominant lifestyle preference across all dietary subgroups. Prevalence of vegan, ovo-lacto-vegetarian and omnivorous diet of school teachers and principals was 2.3%, 5.2%, and 92.5%, respectively. Females were more likely to follow an ovo-lacto-vegetarian diet (6.4% vs. 2.4%; p < 0.01) or vegan/ ovo-lacto-vegetarian (9.0% vs. 4.1%) than males. For total sample, no differences were found across the dietary subgroups considering leisure time physical activity, sports and exercise levels (88.7%; n = 1,197) and weekly engagement in sports (range: 2.9–3.3 days/week), the prevalence of daily fruit consumption (62.4%), alcohol intake (81.5%), or smoking prevalence (11.0%). Vegetable intake was significantly higher among ovo-lacto-vegetarians and vegans (92.9 and 93.5%, respectively; p < 0.01) than in omnivores.ConclusionThis is the first study to investigate the potential differences in basic health behavior among refined dietary subgroups (omnivorous, ovo-lacto-vegetarian, and vegan) in school teachers and principals. The findings indicate that basic diet type differentiation is the first step towards fundamentally healthy behavior, however, further action must be taken to achieve better health among school teachers and principals in Austria (more physical activity, sports and exercise, and fruit and vegetable consumption, less alcohol intake and no smoking).